다공물질 표면처리가 경사판의 증발냉각에 미치는 영향에 관한 실험적 연구 - 이대영; 이재완; 강병하 (대한설비공학회, 2005)
Falling film heat transfer has been widely used in many applications in which heat and mass transfer occur simultaneously, such as evaporative coolers, cooling towers, absorption chillers, etc. In such cases, it is desirable that the falling film spreads widely on the surface forming thin liquid film to enlarge contact surface and to reduce the thermal resistance across the film and/or the flow resistance to the vapor stream over the film. In this work, the surface is treated to have thin porous layer on the surface. With this treatment, the liquid can be spread widely on the surface by the capillary force resulting from the porous structure. In addition to this, the liquid can be held within the porous structure to improve surface wettedness regardless of the surface inclination. The experiment on the evaporative cooling of an inclined surface has been conducted to verify the effectiveness of the surface treatment. It is measured that the evaporative heat transfer increases about 50% by the porous layer treatment as compared with that from orignal bare surfaces.